Zebrafish as a model organism for neurodegenerative disease - Chia, Kelda; Klingseisen, Anna; Sieger, Dirk; Priller, Josef (Frontiers in Molecular Neuroscience, 2022)
The zebrafish is increasingly recognised as a model organism for translational research into human neuropathology. The zebrafish brain exhibits fundamental resemblance with human neuroanatomical and neurochemical pathways, and hallmarks of human brain pathology such as protein aggregation, neuronal degeneration and activation of glial cells, for example, can be modelled and recapitulated in the fish central nervous system. Genetic manipulation, imaging, and drug screening are areas where zebrafish excel with the ease of introducing mutations and transgenes, the expression of fluorescent markers that can be detected in vivo in the transparent larval stages over time, and simple treatment of large numbers of fish larvae at once followed by automated screening and imaging. In this review, we summarise how zebrafish have successfully been employed to model human neurodegenerative diseases such as Parkinson’s disease, Alzheimer’s disease, amyotrophic lateral sclerosis, and Huntington’s disease. We discuss advantages and disadvantages of choosing zebrafish as a model for these neurodegenerative conditions.